Russia and Global Green Transition : Risks and Opportunities - Makarov, Igor; Besley, Daniel; Hasan, Dudu; Boratynski, Jakub; Chepeliev, Maksym; Golub, Elena; Nemova, Vladislava; Stepanov, Ilya (World Bank, Washington, DC, 2021)
Greener economic development in Russia will allow the country to overcome the limits of its current fossil fuel-dependent growth model. It can deliver prosperity to Russia’s citizens that is more sustainable and more resilient to external shocks in a rapidly changing global economy. The choices toward carbon neutrality made by an increasing number of countries and companies bring a new wave of uncertainty to the value of fossil fuel assets. This uncertainty is likely to result in lower and more volatile revenue from exports of hydrocarbons and energy-intensive industrial products.